Additional and temporary protection as a form of protection of forced migrants in Ukraine - Грабова, Яніна Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The article is devoted to the legal regulation of additional and temporary protection. The article analyzes the state of the national law governing the legal status of persons in need of additional or temporary protection in Ukraine, defined relation to other forms of protection of forced migrants. The autor marked the need to improve legal mechanisms for using additional or temporary protection. Protection of asylum seekers is one of the most pressing global problems of the modern world. The purpose of the article was to determine the constitutional and legal features temporary and additional protection disclosure of their relationship with other forms of protection of forced migrants to form recommendations for improving the legislation of Ukraine. The author draws attention to the fact that the problem of forced migrants has become urgent for Ukraine because of its geopolitical position and of the European integration option. Thus, the Ukrainian legislator has provided, in addition to granting legal refugee status such forms of protection of asylum seekers as recognition of the person in need of additional or temporary protection. In 2014, amended the Law of Ukraine "On refugees and persons in need of additional or temporary protection" on 8 July 2011 with order to harmonize national migration legislation with European standards. The definition of additional and temporary protection as contained in Article 1 of the Law of Ukraine "On refugees and persons in need of additional or temporary protection" was brought into compliance with international standards. However, changing the definition without elimination of conflicts with other rules that govern the use of these forms of protection will have no effect. The author of the article specifies exactly which inaccuracies are done by the legislator Thus, it is necessary to take into account that the law must be sufficiently accessible and must have predictable consequences of its use. Means that according to the principle of legal certainty the law should to be formulated in a way that allows each person to act accordingly. The Law of Ukraine "On refugees and persons in need of additional or temporary protection" does not meet these requirements. In addition, both as regards the application of legislation on temporary so for additional protection, has not formed adequate and equal enforcement practices that adversely affects the possibility of their application. Thus, the author notes that the rules governing researched forms of protection of forced migrants are in need of substantial revision. Also, in the article, the author describes the interrelation of additional and temporary protection of the legal status of internally displaced persons. The main criterion that distinguishes the internally displaced persons from other forced migrants is internal character movement. The author believes that the forced migrants who use an additional or temporary protection must be able to obtain the status of internally displaced persons, as citizens of Ukraine. Thus, we can conclude that the article concerns very actual the topic, the author achieved its objectives.